Stigmatizing attitudes and low levels of knowledge but high willingness to participate in HIV management: A community-based survey of pharmacies in Pune, India - Gupta Amita; Sane Suvarna S; Gurbani Ajay; Bollinger Robert C; Mehendale Sanjay M; Godbole Sheela V (BMC, 2010)
Abstract Background The World Health Organization (WHO) recommends that the role of pharmacists in low-income settings be expanded to address the increasing complexity of HIV antiretroviral (ARV) and co-infection drug regimens. However, in many such settings including in India, many pharmacists and pharmacy workers are often neither well trained nor aware of the intricacies of HIV treatment. The aims of our study were; to determine the availability of ARVs, provision of ARVs, knowledge about ARVs, attitudes towards HIV-infected persons and self-perceived need for training among community-based pharmacies in an urban area of India. Methods We performed a survey of randomly selected, community-based pharmacies located in Pune, India, in 2004-2005 to determine the availability of ARVs at these pharmacies, how they were providing ARVs and their self-perceived need for training. We also assessed knowledge, attitudes and perceptions on HIV and ARVs and factors associated with stocking ARVs. Results Of 207 pharmacies included in the survey, 200 (96.6%) were single, private establishments. Seventy-three (35.3%) pharmacies stocked ARVs and 38 (18.4%) ordered ARVs upon request. The reported median number of ARV pills that patients bought at one time was 30, a two week supply of ARVs (range: 3-240 pills). Six (2.9%) pharmacy respondents reported selling non-allopathic medicines (i.e. Ayurvedic, homeopathy) for HIV. Ninety (44.2%) pharmacy respondents knew that ARVs cannot cure HIV, with those stocking ARVs being more likely to respond correctly (60.3% vs. 34.8%, p = 0.001). Respondents of pharmacies which stocked ARVs were also more likely to believe it was a professional obligation to provide medications to HIV-infected persons (91.8% vs. 78.8%, p = 0.007) but they were also more likely to believe that HIV-infected persons are unable to adhere to their medicines (79.5% vs. 40.9%, p < 0.01). Knowledge of the most common side effects of nevirapine, abnormal liver enzyme profile and skin rash, was reported correctly by 8 (3.9%) and 23 (11.1%) respondents, respectively. Seven (3.4%) respondents reported that they had received special training on HIV, 3 (1.5%) reported receipt of special training on ART and 167 (80.7%) reported that they believed that pharmacy staff should get special training on ART. Conclusion There is a high willingness to participate in HIV management among community-based pharmacies but there is a tremendous need for training on HIV therapies. Furthermore, stigmatizing attitudes towards HIV-infected persons persist and interventions to reduce stigma are needed, particularly among those that stock ARVs.